Synthesis, X-ray characterization and theoretical study of 3a, 6:7, 9a-diepoxybenzo[de]isoquinoline derivatives: on the importance of F⋯O interactions. (14th November 2020) - Grudova, Mariya V.; Gil, Diego M.; Khrustalev, Victor N.; Nikitina, Eugeniya V.; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Kletskov, Alexey V.; Frontera, Antonio; Zubkov, Fedor I.
Abstract : This manuscript reports the synthesis, X-ray characterization and theoretical study of 3 a, 6:7, 9 a -diepoxybenzo[ de ]isoquinoline derivatives focusing on the importance of F···O interactions. Abstract : The synthesis, X-ray characterization and Hirshfeld surface analysis of a series of tetrahydro-diepoxybenzo[ de ]isoquinoline derivatives obtained by the tandem [4+2] cycloaddition between perfluorobut-2-yne dienophile (F3 C–CC–CF3 ) and a row of N, N -bis(furan-2-ylmethyl)-4-R-benzenesulfonamides (bis-dienes, R = Me, F, Cl, Br, I) are reported in this manuscript. The implementation of kinetic/thermodynamic control allowed us to obtain both "pincer"- and "domino"-type adducts in good/moderate yields. In the solid state, most of the pincer adducts form self-assembled dimers (R = Me, Cl, Br, I) and, contrariwise, the domino adducts form 1D supramolecular chains, which are described in detail herein. Remarkably, in the self-assembled dimers, bifurcated halogen bonds involving one fluorine atom of the CF3 group and both O-atoms of sulfonamide are formed, which have been analyzed using DFT calculations, and the QTAIM and NCIplot computational tools.